Clearance of seborrhoeic keratoses with topical dobesilate. (22nd June 2012) - Cuevas, Pedro; Angulo, Javier; Salgüero, Irene; Giménez-Gallego, Guillermo
Abstract : A patient with two seborrhoeic keratoses in the face received a single daily application of dobesilate cream during 6 months. Dobesilate achieved complete clearance of the seborrhoeic keratosis lesions with good cosmoses, suggesting that this compound is a safe and efficient candidate in the treatment of seborrhoeic keratoses.